EFL LEARNERS’ PRODUCTION OF IDIOMATIC EXPRESSIONS IN SPEAKING - Yunie Amalia Rakhmyta; Rusmiati (Jurnal As-Salam, 2020)
Idiomatic expressions are expressions whose meanings cannot be derived from their literal meaning. Thus, it is viewed as a challenging part for EFL learners in either understanding or practicing them. However, using them in oral spoken adequately signifies that someone is a proficient English user. This research is carried out to depict the learner's application of idiomatic expressions in spoken English. It is performed to address the accompanying examination questions: (1) Do EFL learners of the English Department in IAIN Takengon use idiomatic expressions in speaking? (2) What type of idioms do they produce in speaking? (3) What is the most frequently used idiom type in their speaking?. 20 students' recordings were collected and analyzed using the descriptive qualitative method. The result shows that the learners use idiomatic expressions. The learners produced only three types of idiomatic expressions, namely phrasal verb idiom, tournures idiom, and irreversible compound idiom. Of all, phrasal verb idiom is the most frequently used. It is suggested that the learners are encouraged to be exposed to English more often to apply more idiomatic expressions in their speaking.